KUALITAS PELAYANAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN WAROPEN - , Inansih H R Kolimo; , Dr. Nunuk Dwi Retnandari., MS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Public service delivery by the public today is not quite satisfactory, it is seen by the many complaints and dissatisfaction as service recipients, compounded by the practices of Corruption, Collusion and Nepotism form of deviant behavior in the provision of public services.In this study two important questions we wanted to answer, namely: 1) What is the quality of public services of Population and Civil Registration Waropen, and 2) the factors that affect the quality of public services. The method used in this study is a qualitative method. To measure the quality of service of Population and Civil Registration Waropen in deed using three indicators, namely clarity of information, the attitude of officers and comfortable environment, while influencing factors, namely discretionary authority, the ability of the apparatus, and a system of incentives. The results showed that the quality of public services in the Department of Population and Civil Registration Waropen deed is still lacking in quality. This can be measured from the level of clarity of the overall cost of service information, and the unavailability of infomrasi about the timing of the service. Attitude level officials can be seen from the persistence of discriminatory attitudes of service personnel, while the comfort level of the environment seen as a means of incomplete heat of the waiting room and the narrow parking space. The low quality of public services of Population and Civil Registration Waropen influenced by the low ability of service personnel in the use of discretionary authority looks to still awaiting instructions based on the boss and the guidelines, lack of rigor in deed and unclear criteria for awarding incentive system.To improve the quality service it is suggested, namely: 1) Make the service standard service procedures, cost of service, turnaround time openly informed services